2020
DOI: 10.20517/2347-9264.2020.121
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between hyaluronidase and hyaluronic acid gel fillers - a review of the literature and comparative analysis

Abstract: Hyaluronic acid (HA) is the most common component of aesthetic fillers. Many formulations exist, each exhibiting properties that are manifestations of individual molecular modifications. The enzyme hyaluronidase degrades hyaluronic acid and can therefore be injected into soft tissue to reduce suboptimally placed HA fillers or to reverse local ischemic complications. The clinically available varieties of hyaluronidase may be derived from crude animal extracts or genetically engineered from recombinant human DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…Also, no consensus was established on which type of hyaluronidase is most superior in dissolving HA fillers. 17 A blind randomized study on the reversal of HA filler injection had demonstrated comparable efficacy between the use of 20 and 40 U ovine hyaluronidase in reducing the volume of 0.2 mL HA filler bolus implants based on significantly lower palpation scores compared to non-treated and saline-treated HA filler implants. The study also reported that identical treatments of ovine hyaluronidase showed no clinically significant difference in HA filler volume reduction among different filler implants from three major HA filler manufacturers, despite variability in cohesive properties, HA content and degree of crosslinking.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, no consensus was established on which type of hyaluronidase is most superior in dissolving HA fillers. 17 A blind randomized study on the reversal of HA filler injection had demonstrated comparable efficacy between the use of 20 and 40 U ovine hyaluronidase in reducing the volume of 0.2 mL HA filler bolus implants based on significantly lower palpation scores compared to non-treated and saline-treated HA filler implants. The study also reported that identical treatments of ovine hyaluronidase showed no clinically significant difference in HA filler volume reduction among different filler implants from three major HA filler manufacturers, despite variability in cohesive properties, HA content and degree of crosslinking.…”
Section: Discussionmentioning
confidence: 98%
“…The Juvéderm family of products (AbbVie/ Allergan) uses their proprietary "Hylacross" and "Vycross" technology to manufacture monophasic HA fillers, whereas the Restylane family of products (Galderma) manufacture their biphasic HA dermal fillers using their proprietary non-animal stabilized HA (NASHA) and more recently, "XpresHAn" technology. [15][16][17] Another series of BDDE-crosslinked HA dermal fillers was recently introduced in South Korea. The Neuramis family of products (NEU series, Medytox, Inc.) are monophasic HA dermal fillers manufactured using stabilized HA through purification and enhancement (SHAPE) technology, generating products with varying degree of crosslinking to suit specific clinical indication.…”
Section: Introductionmentioning
confidence: 99%
“…All HA dermal fillers in the NEU series are manufactured as having a mono-phasic gel phase similar to BEL fillers, 40–42 and is very distinct from the bi-phasic gel phase of RES fillers. 42 , 43 Mono-phasic HA dermal fillers consist of a mixture of high- and low-molecular weight HA, 15 , 19 whereas bi-phasic HA dermal fillers consist of cross-linked HA admixed with non-crosslinked HA. 44 Mono-phasic fillers have been reported to show higher cohesivity (ie, higher affinity between the gel molecules) and lower viscoelasticity than bi-phasic fillers.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors can explain these differences: HA concentration, molecular weight, crosslinking technology and amount of free HA present in the final product 23,29 . Many authors report crosslinking density as the factor with the greatest influence on the rheological properties, specifically the stiffness of the gel 25,30,31 …”
Section: Methods Currently Used To Characterize Ha Dermal Fillersmentioning
confidence: 99%